EXPLORING TEACHER FEEDBACK STRATEGIES IN ENHANCING SENIOR HIGH SCHOOL STUDENTS WRITING SKILL IN CIREBON CITY - Siti Lina Nurlina; Virga Putra Darma; Dwi Nopiyadi (Tomorrow's Education Journal, 2025)
This research investigates teacher feedback strategies in enhancing senior high school students’ writing skills in Cirebon City. The study was motivated by the frequent writing errors made by students and the need to understand how teacher feedback can address these errors effectively. Guided by Vygotsky’s Sociocultural Theory and Hattie and Timperley’s feedback model (2007), this study also employed Dulay et al.’s Surface Strategy Taxonomy (1982) to classify students’ writing errors. A qualitative case study design was used, with data collected from one English teacher and 35 students at Senior High School 2 Cirebon through classroom observations, interviews, and document analysis. The findings reveal that misformation errors were the most frequent, followed by omission, addition, and misordering errors. The teacher provided four types of feedback: task, process, self-regulation, and personal feedback. Students responded positively to the feedback, showing improved awareness of grammar and writing quality in their subsequent drafts. It can be concluded that teacher feedback plays a crucial role in reducing errors and supporting both the technical and motivational aspects of students’ writing development.